2011
DOI: 10.1530/joe-11-0034
|View full text |Cite
|
Sign up to set email alerts
|

eNOS activation and NO function: Differential control of steroidogenesis by nitric oxide and its adaptation with hypoxia

Abstract: Nitric oxide (NO) plays a role in a wide range of physiological processes. Aside from its widely studied function in the regulation of vascular function, NO has been shown to impact steroidogenesis in a number of different tissues. The goal of this review is to explore the effects of NO on steroid production and further, to discern its source(s) and mechanism of action. Attention will be given to the regulation of NO synthases in specific endocrine tissues including ovaries, testes, and adrenal glands. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 100 publications
1
30
0
Order By: Relevance
“…Besides cAMP signalling, NO-cGMP pathway is also involved in the regulation of Leydig cell steroidogenesis (reviewed in Ducsay & Myers, 2011). Results of this study showed that NO-cGMP signalling was more affected by Doxa-treatment independent of its duration.…”
Section: (A) (B) (D) (C)mentioning
confidence: 77%
“…Besides cAMP signalling, NO-cGMP pathway is also involved in the regulation of Leydig cell steroidogenesis (reviewed in Ducsay & Myers, 2011). Results of this study showed that NO-cGMP signalling was more affected by Doxa-treatment independent of its duration.…”
Section: (A) (B) (D) (C)mentioning
confidence: 77%
“…For example, the adrenal glands and ovaries of humans use LDL-derived cholesterol to produce steroid hormones (42)(43)(44). Nitric oxide inhibits steroid production ( 45 ), and the high levels of dab2 expressed in steroidogenic tissues ( 46,47 ) may facilitate LDL uptake when nitric oxide levels are low and cholesterol demand for steroid production is high. More generally, activation of ERK induces LDLR expression in dividing cells to supply the cholesterol needed for membrane biogenesis ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that angiotensin II stimulates aldosterone production in H295R cells through AT1 receptor coupled to PLC, increasing the production of InsPn (Rainey et al 2004). Although HA inhibited H295R cell proliferation by increasing InsPn levels without activating aldosterone production, it is possible that HA stimulates NOS enzyme activity (via Ca 2C ), blocking steroidogenesis as described previously for MA-10 LCs by us (Mondillo et al 2009) and has been observed in other steroidogenic systems (Ducsay & Myers 2011). Regarding this, it has been demonstrated that NOS can inhibit L-type calcium channels (Wang et al 2008), which are necessary for AII-mediated steroidogenesis.…”
Section: Discussionmentioning
confidence: 62%